A study of maternal mortality due to non-obstetric causes - Kansara, Tejal N.; Shah, Tushar M.; Lalcheta, Foram R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy, although being considered a physiological state, carries the risk of serious maternal morbidity and at times mortality, due to various complications that may arise during pregnancy, labour or thereafter. The existing medical condition, infection, and surgical condition which is collectively called as non- obstetric cause pre disposes a women for more complication than a non-pregnant women, so much so that it can lead to maternal mortality. Thus, Pregnancy is more vulnerable state and present study was carried out to study, analyse and review various non-obstetrics causes of death of women during pregnancy or within 42 days of termination of pregnancy in Tertiary care centre. Methods: This was an Observational study, conducted in the department of obstetrics and gynaecology, at a tertiary care hospital attached with medical college, from October 2016 to October 2018. The details of maternal deaths were collected from various departments with non- obstetric causes and analyzed. Results: The total number of deliveries in my study period was 15,208. There were 197 maternal mortality in our study period, of which 51 women died of non-obstetric causes. The most common cause of maternal mortality in our study was hepatic cause i.e. 33.33% amongst which viral hepatitis was the most common cause followed by respiratory (19.60%), infectious (15.18%), heamoglobinopathy (13.72%), cardiac (5.88%), neurological (5.88%), surgical (5.88%) causes. Conclusions: Looking into our study, maternal mortality can be reduced by identifying various different indirect medical causes which are preventable by proper pre-pregnancy evaluation for pre-existing comorbid conditions.